Redox (phospho)lipidomics of signaling in inflammation and programmed cell death. Issue 1 (9th May 2019) - Tyurina, Yulia Y; St. Croix, Claudette M; Watkins, Simon C; Watson, Alan M; Epperly, Michael W; Anthonymuthu, Tamil S; Kisin, Elena R; Vlasova, Irina I; Krysko, Olga; Krysko, Dmitri V; Kapralov, Alexandr A; Dar, Haider H; et al.
Abstract: In addition to the known prominent role of polyunsaturated (phospho)lipids as structural blocks of biomembranes, there is an emerging understanding of another important function of these molecules as a highly diversified signaling language utilized for intra- and extracellular communications. Technological developments in high-resolution mass spectrometry facilitated the development of a new branch of metabolomics, redox lipidomics. Analysis of lipid peroxidation reactions has already identified specific enzymatic mechanisms responsible for the biosynthesis of several unique signals in response to inflammation and regulated cell death programs. Obtaining comprehensive information about millions of signals encoded by oxidized phospholipids, represented by thousands of interactive reactions and pleiotropic (patho)physiological effects, is a daunting task. However, there is still reasonable hope that significant discoveries, of at least some of the important contributors to the overall overwhelmingly complex network of interactions triggered by inflammation, will lead to the discovery of new small molecule regulators and therapeutic modalities. For example, suppression of the production of AA-derived pro-inflammatory mediators, HXA3 and LTB4, by an iPLA2 γ inhibitor, R-BEL, mitigated injury associated with the activation of pro-inflammatory processes in animals exposed to whole-body irradiation. Further, technological developments promise to make redox lipidomics a powerful approach in the arsenal of diagnostic and therapeutic instruments for personalized medicine of inflammatory diseases and conditions. Graphical Abstract: Review on free and esterified into phospholipids polyunsaturated fatty acids as signals controlling inflammation and cell death.